Visualizing Humans Contributions to Tax Complience Research: A Bibliometric Analysis - Arifin, Firmansyah; Fitri, Nuri Annisa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Understanding the factors influencing taxpayer compliance with tax laws continues to be a focal point for many researchers. This study presents a bibliometric and visual analysis of tax compliance, particularly focusing on the research clusters related to tax compliance, covering studies published between 1977 and 2024 and indexed in the Dimensions database. The analysis aims to provide insights and guidance for future research in the field of tax compliance. A total of 500 studies on Tax Compliance were identified in the Dimensions database, with the majority being articles published in international journals. Australia, Austria, Canada, Italy, and the United States emerged as the most productive countries in terms of Tax Compliance publications. Additionally, a notable trend is the increasing number of multidisciplinary studies conducted by authors from various countries, particularly concerning human factors. This study recommends exploring multiple databases and refining future research through several clusters identified from these findings. Thus, researchers can gain a more comprehensive understanding of the complexity of Tax Compliance and the various clusters influencing it. The bibliometric mapping and visualization of Tax Compliance provide a foundation for advancing knowledge and promoting informed investigations in the field of human behavior regarding tax compliance